Antifungal activity of Chaetomium globosum transformated with an endochitinase gene, chbi, from Trichoderma viride - LU Jian-ping; LIN Fu-cheng; LI De-bao (浙江大学学报. 农业与生命科学版, 2006)
In order to find out the roles of endochitinase during biocontrol process in Chaetomium globosum, a 42 kDa endochitinase gene (chbi) cloned from the genomic DNA of Trichoderma viride was transferred to C. globosum isolates CG10 and CG12 separately by fungal transformation vector pECHBI. The endochitinase activities of one-fifth transformants with a foreign endochitinase gene (chbi) were enhanced significantly. The antagonism effectiveness of C. globosum transformants against nine pathogen fungi (Pythium aphanidermatum, Rhizoctonia solani, Fusarium oxysporum f. sp. Cumumerinum, Altermaria alternata, Sclerotium rolfsii, Pestalotia diospyri, Pythium ultimum and Colletotrichum piperatum) was assessed in PDA culture medium. The transformant CG10-26 exbihited higher inhibition on the growth of F. oxysporum than the wild type CG12 in the confrontation culture on PDA plate. The antifungual activities of the organic substances secreted by the transformant CG12-14 and CG12-25 cultured on the cellophane paper in the PDA culture medium exhibited higher inhibition on the growth of A. alternata than the wild type CG12. The antifungual activities of transformants CG12-18 and CG12-21 against P. diospyri, transformant CG12-14 against S. rolfsii, and transformant CG12-21 against P. ultimum were increased as those of CG12-14 and CG12-25 on the cellophane paper against A. alternata. There are no obvious relationships between the antifungual activities and the endochitinase activities in C. globosum transformants. For particular antagonism mechanism and pathogen fungus, the way to reach the great biocontrol effectiveness of transformants is to use the pertinent resistance-related gene.